2019
DOI: 10.1101/865147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a functional small non-coding RNA encoded by African swine fever virus

Abstract: 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…3a; see also Table S9 in the supplemental material); these could provide a rich hunting ground for small noncoding RNAs (sncRNAs). One TSS cluster associated with an sncRNA gene (at position 71302 on the BA71V genome) was previously reported by Dunn et al (51) as ASFVsRNA2, that is encoded in the antisense orientation relative to that of the ASFV RNA polymerase subunit RPB6-encoding gene. Further investigation of antisense sncRNAs in the BA71V transcriptome may uncover further examples of riboregulation, i.e., a more complex method of modulating its own or host gene expression beyond the protein level.…”
Section: Discussionmentioning
confidence: 76%
“…3a; see also Table S9 in the supplemental material); these could provide a rich hunting ground for small noncoding RNAs (sncRNAs). One TSS cluster associated with an sncRNA gene (at position 71302 on the BA71V genome) was previously reported by Dunn et al (51) as ASFVsRNA2, that is encoded in the antisense orientation relative to that of the ASFV RNA polymerase subunit RPB6-encoding gene. Further investigation of antisense sncRNAs in the BA71V transcriptome may uncover further examples of riboregulation, i.e., a more complex method of modulating its own or host gene expression beyond the protein level.…”
Section: Discussionmentioning
confidence: 76%
“…Ssc_circ_009380 was found to promote the activation of NF-κB pathway in the inflammatory response to TGEV by binding miR-22 [63]. Differentially expressed ln-cRNAs might be involved in inflammatory responses induced by TGEV via acting as miRNA sponges, regulating their upstream and downstream genes [64]. Data analysis based on enrichment of Gene Ontology of host target genes demonstrated that the differentially expressed miRNAs participated in regulatory networks, including cellular process, metabolic process, and immune system response [65].…”
Section: Transmissible Gastroenteritis Virus Infection and Host Ncrnasmentioning
confidence: 99%
“…Overexpression of ASFVsRNA2 led to up to a 1 log reduction in ASFV growth indicating that ASFV utilized a virally encoded small RNA to disrupt its own replication. Further study showed that ASFVsRNA2 had a variable number of 3′ U residues and it did not fit the classic miRNA biogenesis pathway, so called the canonical miRNA biogenesis pathway; therefore, ASFVs-RNA2 cannot be viewed as miRNA [64].…”
Section: Ncrnas Expressed By African Swine Fever Virusmentioning
confidence: 99%